Histomorphologic and Histomorphometric Characteristics of Zygapophyseal Joint Remodeling in Ankylosing Spondylitis. Issue 7 (July 2014) - Bleil, Janine; Maier, Rene; Hempfing, Axel; Schlichting, Uwe; Appel, Heiner; Sieper, Joachim; Syrbe, Uta
<x xml:space="preserve">Abstract</x> Objective To unravel the mechanisms that control bony ankylosis in ankylosing spondylitis (AS). Methods Histomorphologic and histomorphometric analyses were performed on zygapophyseal joints obtained from 18 patients with AS, 9 patients with osteoarthritis (OA), and 10 cadaver donors without a rheumatic disease (controls). The proteoglycan content of the cartilage was determined by Safranin O staining and the chondrocyte apoptosis according to caspase 3 expression. Results AS joints were categorized into 3 groups according to the morphology of the joint surfaces and joint space: group 1 were joints with an open joint space, group 2 were joints with cartilaginous fusion, and group 3 were joints with bony fusion of the joint surfaces. Progressive loss of the joint space from group 1 joints to group 3 joints suggests that this grouping corresponds to sequential stages of joint remodeling. Cartilage thickness and subchondral bone plate thickness declined from group 1 to group 3 (P < 0.01). Increased chondrocyte apoptosis rates were found in groups 1 and 2 (P < 0.05), while in group 3, a reduction in the proteoglycan content was found (P < 0.001). Bone marrow replacement and invasion of the subchondral bone plate by fibrous tissue was found predominantly in AS joints in group 2. Conclusion Cartilage degeneration, indicated by cartilage thinning, enhanced chondrocyte apoptosis, and proteoglycan loss, and subchondral bone thinning, promoted by invasion of the subchondral bone plate by a fibrous tissue originating from the bone marrow, are hallmarks of joint remodeling in AS.